Implementasi Kit IPA Alternatif dari Barang Bekas terhadap Motivasi dan Pemahaman Konsep IPA Peserta Didik Sekolah Dasar - Syahrial Ayub; I Wayan Gunada; Muh Makhrus; Sutrio Sutrio (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
This study aims to determine the implementation of alternative science kits made from recycled materials on elementary school students’ motivation and understanding of science concepts. The study employed a Research and Development (R&D) method using the Borg & Gall development model, which includes the stages of preliminary information gathering, planning, product development, testing, revision, and final product implementation. The alternative science kits were developed using simple materials and recyclable waste materials that are easily found in the surrounding environment, such as plastic bottles, cardboard, straws, used wood, and other recycled materials. The developed products included a simple submarine, hydrostatic pressure apparatus, water wheel, air rocket, magic egg experiment, miniature volcano, and simple electricity generator. The research subjects were students of SD Negeri 6 Mataram. Data collection techniques included observation, student response questionnaires, and science concept understanding tests. The results showed that the use of alternative science kits was able to create a more active, engaging, and interactive science learning environment. Students were more enthusiastic in participating in learning activities because they could conduct experiments directly. Questionnaire results indicated that 78% of students strongly agreed with the use of alternative science kits in science learning. The use of simple teaching aids also helped students understand science concepts more concretely through direct experience and simple experimental activities. Therefore, alternative science kits made from recycled materials can serve as an innovative and economical solution to improve elementary school students’ motivation and understanding of science concepts.